Fully integrating upper-secondary vocational and academic courses: A flexible new way?. (December 2016) - Polidano, Cain; Tabasso, Domenico
Highlights: Fully integrating upper-secondary VET courses into an academic curriculum is seen as a way of avoiding streaming. Taking an integrated VET course is associated with lower academic achievement and reduced chance of university entry. Courses that try to accommodate the conflicting needs of academic and vocationally oriented students may be compromised. Abstract: The tracking of students in upper-secondary school is often criticised for narrowing the post-secondary pathways of student in the vocational education and training (VET) track, which can stigmatise VET. To tackle this problem, countries have introduced courses that integrate aspects of VET and academic study, which provide the dual purpose of preparing students for work and vocational study and providing university pathways for more academic students in the VET track. In this study we assess the latter purpose by examining the outcomes of university aspirants who take these courses in their final year of school. Using rich survey and administrative data from Australia and propensity score matching we find that these courses are associated with lower academic performance and a lower chance of attaining a university offer. Decomposition results show that poor performance in integrated courses is the main driver, which points to potential tension between the two purposes.